ACUTE APPENDICITIS MANAGEMENT: HISTORICAL INSIGHTS, MODERN APPROACHES, AND FUTURE PERSPECTIVES - Przemysław Siemiątkowski; Agnieszka Kiedik; Kacper Zima; Zuzanna Pietruk; Jakub Chamier-Gliszczyński; Dominik Ryszard Płaza; Julia Kozłowska; Sylwia Skraińska (International Journal of Innovative Technologies in Social Science, 2026)
Objectives: This narrative review aims to summarize the historical evolution, current manage-ment strategies, and emerging future directions in the treatment of acute appendicitis, emphasiz-ing the transition from historically fatal disease to modern, evidence-based care.Methods: A thorough review of the literature was conducted, summarizing historical medical texts, surgical publications, and recent clinical guidelines. Emphasis was placed on the evolu-tion of surgical techniques, antibiotic therapy, and non-operative management strategies, as well as recent innovations in minimally invasive and personalized care.Key Findings: Acute appendicitis represents a heterogeneous disease spectrum requiring indi-vidualized management. While open appendectomy historically served as the gold standard, laparoscopic appendectomy is now the first-line operative approach in most cases. Non-operative management with antibiotics is a viable option in carefully selected patients with un-complicated disease, although recurrence and treatment failure remain concerns. Management of complicated appendicitis continues to rely on timely source control, with selective use of con-servative and interventional strategies. Emerging trends include ambulatory surgery, personal-ized treatment algorithms, and experimental endoscopic approaches.Conclusions: Advances in surgical technique, antimicrobial therapy, and perioperative care have dramatically reduced appendicitis-related morbidity and mortality. Contemporary man-agement emphasizes patient selection, minimally invasive surgery, and value-based care. Future progress will depend on high-quality evidence supporting personalized and resource-efficient treatment pathways.